Fighting stigma of mental illness in midsize European countries - Beldie, Alina (2013)
Purpose Stigma is the most powerful obstacle to the development of mental health care. Numerous activities aiming to reduce the stigma of mental illness and the consequent negative discrimination of the mentally ill and their families have been conducted in Europe. Descriptions of many of these activities are not easily available, either because there are no publications that describe them, or because descriptions exist only in local languages. This supplement aims to help in overcoming this imbalance by providing a description of anti-stigma activities in 14 countries in Europe regardless of the language in which they were published and regardless whether they were previously published.